Public Policy Issues in the Context of Public Sector Reforms: A Qualitative Storytelling of a Former Government Department in the Asia-Pacific Region - Anup Chowdhury; Nikhil Chandra Shil (Asia-Pacific Journal of Public Policy, 2023)
Predominantly public policy is a set of guidelines initiated by the government of a country to work in favour of mass people or the public. We showcase and represent public policy materials against the backdrop of being involved in the process of accountability, transparency, and efficient and effective administration and program delivery. In addition, the selected government department used private-sector management control technologies to deal with the public-sector reform initiatives. These elements are considered part of the modern approach to public administration also. The study may be useful to policymakers formulating new public sector policies. Moreover, the findings reported in this study would be useful to public sector managers in their daily decision-making process.